PSYCHOLOGICAL WELL BEING OF EMERGING ADULTS IN RELATION TO THEIR PARENTS DURING PANDEMIC COVID-19 - Dinardinata, Adi; Fatmasari, Agustin Erna; Indrawati, Endang Sri (Jurnal Psikologi, 2023)
Relations with parents have a lot of influence because emerging adults with student status are spending more time at home during pandemic. This study aims to describe the psychological well-being of emerging adults during the Covid-19 pandemic. The research method used is a phenomenological qualitative approach with InterpretativePhenomenological Analysis. Data were obtained through in-depth interviews, involving six respondents consisting of 3 girls and 3 boys selected by purposive sampling technique. The inclusive criteria are emerging adults, live at home with their parents during the pandemic, and willing to become respondents. The result were six themes related to psychological well-being, namely feelings during a pandemic, difficulties experienced,solutions to overcome them, relationships with parents, support provided by parents, and hopes related to a pandemic situation. An interesting finding in this study is that respondents who have positive or negative relationships with their parents will still be able to achieve psychological well-being. The difference is that the process of respondents with negative relationships is more difficult than respondents with positive relationships.Emerging adults must be able to find the meaning of life so that in difficult situations they can still be independent and adapt well.